PENERAPAN PEMBELAJARAN ONLINE DENGAN MODEL PROJECT BASED LEARNING (PBL) TERHADAP HASIL BELAJAR PESERTA DIDIK - Gusniarty Simanjuntak; Riska Septia Wahyuningtyas; Jendri Mamangkey (Inteligensi : Jurnal Ilmu Pendidikan, 2022)
This study was conducted to determine the application of online learning with the Project Based Learning (PBL) model on student learning outcomes. This research was classified as a quasi-experimental, with a sample of 36 students of class XI IPA 1 and IPA 2 at SMA Negeri 1 Siborongborong as the control class and the experiment through purposive sampling technique. The results show that there is an increase in the value, where previously only 65.94 increased to 82.06. In addition, further ANOVA test was also carried out with sig. 0.023 0.05 which indicates that PBL learning has an effect where the PBL model is better than conventional learning, which shows that there is a difference in the average learning outcomes of control and experimental class students. This is because the advantages of PBL are able to construct and provide opportunities to convey, listen and reflect on ideas based on individual experiences in groups so that they are able to provide meaningful learning during online learning